P16 Assessment of myocardial fibrosis activity using 18f-fluoroproline positron emission tomography (pet) in rat models of cardiovascular disease. (5th April 2020) - Balogh, Viktoria; Spath, Nick; Alcaide-Corral, Carlos; Walton, Tashfeen; Lennen, Ross; Jansen, Maurits; Lucatelli, Christophe; Newby, David E; MacAskill, Mark; Hadoke, Patrick; Gray, Gillian A; Tavares, Adriana AS
Abstract : Background: Fibrosis is a fundamental process involved in healing and remodelling post myocardial infarction (MI) and during heart failure (HF). Positron emission tomography (PET) is a potential tool for investigating active collagen biosynthesis in the myocardium with fluoroprolines. We hypothesised that 18F-fluoroprolines can identify either triple helix collagen (trans-4-18F-fluoro-L-proline, e.g.scar tissue) or single-chain polypeptide abnormal collagen (cis 4 18F fluoro L proline, e.g.interstitial fibrosis) by directly targeting collagen biosynthesis. Methods: Adult male Sprague-Dawley rats underwent total left coronary artery occlusion to induce MI. Seven days after MI, animals underwent magnetic resonance imaging (MRI) and were injected with trans- or cis-4-18F-fluoro-L-prolines for PET imaging. Hearts collected after in vivo imaging were stained with Picrosirius red (PSR) to assess myocardial fibrosis. Another set of rats underwent 4-week angiotensin-II (AngII) treatment (250 ng/kg/min or 500 ng/kg/min), to induce left ventricular hypertrophy and diffuse fibrosis, with blood pressure checks and ex vivo assessment of myocardial collagen content (PSR stain; hydroxyproline (HP) assay), to develop a model of interstitial fibrosis for future PET imaging studies. Results: Uptake of trans-fluoroproline was strongest in the infarct area and cis-fluoroproline was strongest in the remote myocardium (mean standard uptake value ratio of 1.3 vs 0.7). The trans-fluoroproline SUVr strongly, and inversely correlated with ventricular ejection fraction (r2=0.93) and scar tissue size, as determined by MRI, and areas of fibrosis determined by PSR staining. Following AngII treatment, blood pressure significantly increased in both treatment groups by week 2 and stayed high until the end of the study in the high dose group compared to baseline. PSR analysis of heart tissue (AngII study-arm) showed a trend towards increased% fibrosis in the myocardium in the high dose group compared to controls. HP levels were significantly increased with high dose treatment compared to controls (mean: 0.7 vs 0.37 µg/mg; ANOVA p<0.01). PSR values significantly correlated with HP measurements (global heart: p=0.0016). Conclusions: Fluoroproline PET imaging could identify and quantify fibrosis activity in vivo following MI and the results validated with histological markers of fibrosis. Based on the results so far, the development of the diffuse fibrosis model to mimic hypertensive HF is promising. Future PET imaging studies with 18F-fluoroprolines and the model of hypertensive heart failure are ongoing.